Synthesis and X-ray Structure of a Novel N´ -Ferrocenylmethyl-N´ -phenylbenzohydrazide - Terki, B.; Lanez, T.; Belaidi, S.; Gornitzka, H.; Ourari, A. (Asian Journal of Chemistry, 2010)
Reaction of ferrocenylmethyltrimethylammonium iodide with N´-phenylbenzohydrazide afforded a novel stable N´-ferrocenylmethyl-N´-phenylbenzohydrazide which was characterized by 1H and 13C NMR, mass spectroscopy and X-ray crystallography. The product crystallizes in the orthorhombic space group Pbca. The structure analysis confirms the optimized geometry obtained by molecular modelling calculations. The electrochemical behaviour of the N´-ferrocenylmethyl-N´-phenylbenzohydrazide derivative has been studied by cyclic voltammetry.